2011
DOI: 10.1124/dmd.111.043273
|View full text |Cite
|
Sign up to set email alerts
|

Excretion, Metabolism, and Pharmacokinetics of 1-(8-(2-Chlorophenyl)-9-(4-Chlorophenyl)-9H-Purin-6-yl)-4-(Ethylamino)Piperidine-4-Carboxamide, a Selective Cannabinoid Receptor Antagonist, in Healthy Male Volunteers

Abstract: ABSTRACT:The disposition of 1-(8- (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Molecular docking studies of compound 1a with CYP3A4 showed two energetically favored binding clusters (clustered at RMSD 2.0 Å) where either the pyrimidino-piperidine ring ( Fig 2 Panel A) or the terminal N -ethyl moiety ( Fig 2 Panel B) of compound 1a are in proximity to the heme iron of CYP3A4 for aliphatic hydroxylations at the pyrimidino-piperidine ring and N -deethylation reactions, respectively. Other binding clusters that were also energetically favored (1–2 kcal/mol within the lowest-energy binding cluster) but not in an orientation for a typical P450-catalyzed reaction, were not included for analysis, an approach we previously reported [ 23 27 ]. For example, the binding pose with the trifluoromethyl moiety of 1a closest to the heme may also be energetically favored, but no common P450-catalyzed reactions are expected.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular docking studies of compound 1a with CYP3A4 showed two energetically favored binding clusters (clustered at RMSD 2.0 Å) where either the pyrimidino-piperidine ring ( Fig 2 Panel A) or the terminal N -ethyl moiety ( Fig 2 Panel B) of compound 1a are in proximity to the heme iron of CYP3A4 for aliphatic hydroxylations at the pyrimidino-piperidine ring and N -deethylation reactions, respectively. Other binding clusters that were also energetically favored (1–2 kcal/mol within the lowest-energy binding cluster) but not in an orientation for a typical P450-catalyzed reaction, were not included for analysis, an approach we previously reported [ 23 27 ]. For example, the binding pose with the trifluoromethyl moiety of 1a closest to the heme may also be energetically favored, but no common P450-catalyzed reactions are expected.…”
Section: Resultsmentioning
confidence: 99%
“…First, a highly reactive oxonium ion species is generated; this is followed by SN1 nucleophilic attack of a nitrogen or oxygen (Oppenheimer, 1994), with nicotinamide acting as a leaving group. Examples of substrates are rifampin, imatinib (Miao et al, 2012), otenabant, natural toxin 4-ipomeanol (Chen et al, 2006), nitrosamines, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK), 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL) (Peterson et al, 1994), and 6-(1H-pyrazol-4-yl GSH conjugates are first hydrolyzed by GGT to cysteinylglycine conjugates, which are subsequently further hydrolyzed by amino dipeptidase to cysteine conjugates. These conjugates can be either conjugated by N-acetyl transferase to form mercapturic acids or further cleaved by b-lyase to form possible thiol conjugates (Drug-S 4).…”
Section: Adp-ribosyltransferasementioning
confidence: 99%
“…The derived configuration was further structurally optimized using a quantum mechanicsbased spin-unrestricted B3LYP (Becke, three-parameter, Lee-Yang-Parr) density functional theory method in Gaussian 09 (Gaussian, Inc., Wallingford, CT). A split valence basis set, 6-31G**, in which polarization functions were added on both heavy atoms and hydrogens, was implemented as described previously (Miao et al, 2012;Sun, 2012;Sun et al, 2012). The energetically minimized structure of PF-00734200 by density functional theory was then modified by AutoDockTools (Scripps Research Institute, La Jolla, CA) with Gasteiger atomic charges assigned and flexible torsions defined as the docking input file.…”
Section: Extraction Of Metabolites From Biological Samplesmentioning
confidence: 99%